Palaeoenvironmental Interpretation of Late Quaternary Marine Molluscan Assemblages, Canadian Arctic Archipelago - Gordillo, Sandra; Aitken, Alec (Géographie physique et Quaternaire, 2000)
AbstractThis study examines neonto- logical and palaeontological data pertaining to arctic marine molluscs with the goal of reconstructing the palaeoecology of Late Quaternary ca. 12-1 ka BP glaciomarine environments in the Canadian Arctic Archipelago. A total of 26 taxa that represent 15 bivalves and 11 gastropods were recorded in shell collections recovered from Prince of Wales, Somerset, Devon, Axel Heiberg and Ellesmere islands. In spite of taphonomic bias, the observed fossil faunas bear strong similarities to modern benthic molluscan faunas inhabiting high latitude continental shelf environments, reflecting the high preservation potential of molluscan taxa in Quaternary marine sediments. The dominance of an arctic-boreal fauna represented by Hiatella arctica, Mya truncata and Astarte borealis is the product of natural ecological conditions in high arctic glaciomarine environments. Environmental factors controlling the distribution and species composition of the Late Quaternary molluscan assemblages from this region are discussed.